Analisis Valuasi Saham menggunakan Free Cash Flow to Equity (FCFE), Price Earning Ratio (PER) dan Kinerja Keuangan dari sudut pandang Economic Value Added (EVA) - Rani Rachmawati; Arisyahidin Arisyahidin; Abu Talkah (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
ABSTRACT In investing activities, investors have various options to choose financial instruments in the capital market such as stocks and bonds. Stocks are one of the most popular assets in the capital market. However, that investing involves high risks and challenges for investors. To reduce this risk, stock valuation is used before choosing the decision to be taken on the desired stock. Stock valuation is one important thing in investing. The aim is to help investors to minimize the risk of investment through intrinsic value in making investment decisions. The evaluation model for calculating intrinsic value is fundamental analysis with Free Cash Flow to Equity (FCFE) and Price Earning Ratio (PER). In addition, an assessment of financial performance using the Economic Value Added (EVA) point of view is added to determine the company's ability to empower its capital as one of the parameters in investment decisions. By using regression analysis, it is found that EVA is not able to be a predictor of FCFE, while EVA can be a predictor of PER. The results of the calculations, there are not companies that have the results according to the recommendations. Investors or stakeholders can choose the company according to the point of view they want or need, they tend to value stocks by looking at the company's available cash flows or more interested in assessing the company's income and stock prices. According to the calculation results, the results of undervalued stocks in the stock valuation analysis (FCFE/PER) and the lowest negative EVA results from the undervalued stocks can be an option. Keywords: Stock Valuation, Financial Performance, FCFE, PER, EVA